House price responsiveness of housing investments across major European economies - Luca Gattini; Ioannis Ganoulis (European Central Bank (ECB), 2012)
In comparison with the large literature on house prices, housing investments have been studied far less. This paper investigates the behaviour of private residential investments for the six largest European economies, namely: Germany, France, Italy, Spain, the Netherlands and the United Kingdom. It employs a common modelling structure based on an error correction approach and country specific models. First, co-integration among the parsimoniously specified set of fundamental variables is detected in all countries. Second, cross-country differences are found in the responsiveness of private residential investments to real prices and to other relevant factors. Germany has the strongest response of private residential investments to house price changes whereas Italy shows the lowest responses. In Spain investments seem to be primarily related to their lagged component and short-term changes in house prices, and show a poor relationship with deviations from long-term fundamentals. In some countries, the lagged component of residential investments seems to point to a high persistency effect.
Keywords: C2; R30; E22; 330; co-integration; elasticity; error-correction mechanism; Housing investments